PENGARUH PENYULUHAN BABY MASSAGE TERHADAP MINAT IBU DALAM PELAKSANAAN BABY MASSAGE PADA BAYI USIA 0-36 BULAN: THE INFLUENCE OF BABY MASSAGE COUNSELING ON MOTHER'S INTEREST IN IMPLEMENTING BABY MASSAGE ON BABIES AGED 0-36 MONTHS - Sulistyawati, Henny; Yana Eka Mildiana (WELL BEING, 2023)
Growth and development in babies can be achieved optimally if the result of the interaction of various interrelated factors, for example genetic factors, environmental factors, behavioral factors and useful stimulus factors. Babies' gross motor and fine motor skills should be stimulated as early as possible, for example by doing baby massage. Baby Massage is very effective for eliminating fatigue and boredom in babies, swimming will stimulate motor movements in babies because the baby's muscles will develop very well, the body's joints will work optimally, body growth will increase and the body will become flexible. The aim of this research is to determine whether there is an influence of baby massage education on mothers' interest in implementing baby massage for babies aged 0-36 months. The method used is a quasi-experiment methodology with a one group pre and post test design. The results of the research on mothers' interest in implementing Baby Massage showed that most of the interest was high, namely High 20 (64.4%), medium 5 (16.17%), low 6 (19.4%). And mothers' interest in implementing Baby Massage after counseling. overall high 31 (100%). The Wilcoxon test obtained a p-value of 0.000 <α0.05, so Hi was accepted. In conclusion, there is an influence of Baby Massage counseling on mothers' interest in implementing Baby Massage in Murukan Village, Mojoagung District, Jombang Regency. So from these results, it is important to do baby massage for babies aged 0-36 months